Pain Catastrophizing, Fear of Pain, and Depression and Their Association with Female Sexual Pain. (4th December 2019) - Burri, Andrea; Hilpert, Peter; Williams, Frances
Abstract: Introduction: Painful sexual intercourse or dyspareunia is a common complaint among women, affecting 12–21% of premenopausal women. Recent studies have begun to focus on the role of fear avoidance and pain catastrophizing (PC) in genital pain and have consistently highlighted the importance of psych-affective factors in sexual pain. Aim: To establish the importance of PC, fear of pain, and depression for the development and maintenance of female sexual pain. Methods: This longitudinal study was conducted in the United Kingdom to assess sexual pain at 2 different time points, in 2009 and 2013, in a convenience sample of N = 979 British women. Main Outcome Measure: Well-validated questionnaires including the Pain Catastrophizing Scale, the Pain Anxiety Symptom Scale, and the Female Sexual Function Index (recent and lifelong version) were applied. Results: Multilevel modeling showed a strong increase of short-lived sexual pain over the 4 years (π01  = –0.33; P < .001). According to the moderation analyses, only depression influenced the change in short-lived pain over the 4 years (π11  = 0.46; P  = .016). Similarly, only depression turned out to be independently associated with sexual pain when entered into the multiple regression model, as women reporting higher depression levels also reported more sexual pain ( P < 0.05). Clinical Implications: Clinicians should be aware that the mechanisms influencing short-lived sexual pain and changes in sexual pain seem to be different from the more enduring psychological factors that lead to the development and maintenance of "chronic" sexual pain. Strengths & Limitations: A very generic and unidimensional definition of sexual pain was used without information on pain frequency or intensity, and no information on the possible underlying (medical or psychological or both) causes was available. However, as far as we know this represents the first study to use repeated measures to assess how pain changes over a 4-year period and to explore the role of potential psychoaffective risk factors. Conclusion: Among the variables studied, symptoms of depression seemed to be the only independent predictor of lifelong sexual pain, overriding potential influences of pain catastrophizing or fear of pain.